2023
DOI: 10.3390/pharmaceutics15092294
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols Decrease Chemokine Release by Human Primary Astrocytes Responding to Pro-Inflammatory Cytokines

Mikolaj Grabarczyk,
Dominika Ksiazek-Winiarek,
Andrzej Glabinski
et al.

Abstract: Astrocytes are considered to be the dominant cell fraction of the central nervous system. They play a supportive and protective role towards neurons, and regulate inflammatory processes; they thus make suitable targets for drugs and supplements, such as polyphenolic compounds. However, due to their wide range, knowledge of their anti-inflammatory potential remains relatively incomplete. The aim of this study was therefore to determine whether myricetin and chrysin are able to decrease chemokine release in reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…Research has indicated a correlation between an increase in the expression of activated astrocytes and in ammatory cytokines [49][50][51]. Pro-in ammatory cytokines, predominantly produced by activated macrophages, play a pivotal role in regulating in ammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated a correlation between an increase in the expression of activated astrocytes and in ammatory cytokines [49][50][51]. Pro-in ammatory cytokines, predominantly produced by activated macrophages, play a pivotal role in regulating in ammatory responses.…”
Section: Discussionmentioning
confidence: 99%